2015
DOI: 10.1515/znc-2015-0115
|View full text |Cite
|
Sign up to set email alerts
|

Fungal biotransformation of crude glycerol into malic acid

Abstract: Malic acid production from the biodiesel coproduct crude glycerol by Aspergillus niger ATCC 9142, ATCC 10577 and ATCC 12846 was observed to occur with the highest malic acid level acid being produced by A. niger ATCC 12846. Fungal biomass production from crude glycerol was similar, but ATCC 10577 produced the highest biomass. Fungal biotransformation of crude glycerol into the commercially valuable organic acid malic acid appeared feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It has been shown that crude glycerol derived from the production of biodiesel was capable of supporting fungal malic acid synthesis [1,2,30]. In a recent study, A. niger ATCC 9142, ATCC 10577 and ATCC 12846 were found to be capable of producing malic acid on 10% (v/v) crude glycerol after 192 h at 25 • C [34]. Of the three strains, A. niger ATCC 12846 produced the highest malic acid concentration from crude glycerol [34].…”
Section: Malic Acid Production From Biofuel-related Coproductsmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that crude glycerol derived from the production of biodiesel was capable of supporting fungal malic acid synthesis [1,2,30]. In a recent study, A. niger ATCC 9142, ATCC 10577 and ATCC 12846 were found to be capable of producing malic acid on 10% (v/v) crude glycerol after 192 h at 25 • C [34]. Of the three strains, A. niger ATCC 12846 produced the highest malic acid concentration from crude glycerol [34].…”
Section: Malic Acid Production From Biofuel-related Coproductsmentioning
confidence: 98%
“…In a recent study, A. niger ATCC 9142, ATCC 10577 and ATCC 12846 were found to be capable of producing malic acid on 10% (v/v) crude glycerol after 192 h at 25 • C [34]. Of the three strains, A. niger ATCC 12846 produced the highest malic acid concentration from crude glycerol [34]. The ability to produce malic acid from crude glycerol did not seem to be highly correlated with cellular biomass since ATCC 10577 produced a higher biomass level than did ATCC 12846 after 192 h at 25 • C [34].…”
Section: Malic Acid Production From Biofuel-related Coproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…A. niger strains ATCC 9142 and ATCC 10577 were investigated for the production of malic acid from thin stillage, and achieved product titers of 17 and 19 g/L, respectively ( West, 2011 ). When using crude glycerol as feedstock, A. niger ATCC 12486 could produce 23 g/L malic acid after 192 h at 25°C ( West, 2015 ).…”
Section: Malic Acid Production Using Wild Type Microorganismsmentioning
confidence: 99%
“…As global biodiesel production continues to increase, a surplus of the biodiesel coproduct crude glycerol has resulted and lowered the price of crude glycerol to about $0.01/pound [6]. A recent study has found that crude glycerol can be utilized by three strains of Aspergillus niger to produce malic acid [7]. Other fungi or yeast may also be able to utilize crude glycerol to synthesize malic acid.…”
Section: Introductionmentioning
confidence: 99%